Radical Roots: The Shaping of British Columbia - Griffin, Harold (Commonwealth Fund, 1999)
[T]his history is a major contribution in recording the tumultuous times and many sharp battles of the working class in British Columbia. –From introduction by Maurice Rush
OCLC: 44670229
Keywords: British Columbia; British Columbia History; Colombie-Britannique Histoire; History; Populism; Populism British Columbia History; Populisme Colombie-Britannique Histoire; Radicalism; Radicalism British Columbia History; Radicalisme Colombie-Britannique Histoire